ANALISIS FREKUENSI INTI SEL PIKNOSIS EPITEL MUKOSA BUKAL PADA PERAJIN BATIK AKIBAT PAPARAN BAHAN PEWARNA AZO - , AURITA SIWI R.; , Dr. drg. Juni Handajani, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Azo dyes are commonly used in the production process of batik industry. This dyes are cytotoxic to human body and cause cell injury leading to cell death (necrosis). The initial stage of necrosis is pyknosis. Azo dyes entered the human body by inhalation through oropharinx and may trigger the formation of pyknosis on buccal mucosa epithelium. The aim of this study was to know the frequency of pyknosis cell in buccal mucosa epithelium caused by azo dyes. The study used cross-sectional method. Twenty people were assigned as the research subjects, which were divided into two groups, treatment and control group. Ten batik workers who were daily exposed to these chemicals were assigned as treatment group. The control group was a group of people who never contacted with these chemicals. Epithelial cells of the buccal mucosa were collected by swabbing using cytobrush. The modification of Feulgen-Rossenbeck were used as staining method. The frequency of pyknosis cell counted per 1.000 cell under the light microscope and were analyzed using the Independent Sample T-Test (p<0,05). The result showed that the frequency of pyknosis cell in Batik workers were significantly higher, compared to control group (p,0,05). It is concluded that the exposure of azo dyes towards batik workers in Yogyakarta increases the frequency of pyknosis cells in buccal mucosa epithelium. The increase of pyknosis frequency is in line with the time of exposure, and is started from ten up to 23 years of exposure.